Enhanced Maximal Upper-Body Strength Increases Performance in Sprint Kayaking. Issue 4 (18th April 2023) - Kristiansen, Mathias; Pedersen, Ann-Marie Sydow Krogh; Sandvej, Ghita; Jørgensen, Patrick; Jakobsen, Jarl Venneberg; de Zee, Mark; Hansen, Ernst Albin; Klitgaard, Kent K.
Abstract: Kristiansen, M, Sydow Krogh Pedersen, A-M, Sandvej, G, Jørgensen, P, Jakobsen, JV, de Zee, M, Hansen, EA, and Klitgaard, KK. Enhanced maximal upper-body strength increases performance in sprint kayaking. J Strength Cond Res 37(4): e305–e312, 2023—The association between upper-body strength and performance in 200-m flat-water sprint kayak is not fully elucidated. Therefore, the aim of study 1 was to investigate the relationship between upper-body strength and kayaking performance. In study 2, the aim was to perform a randomized training intervention to investigate whether a causal relationship was present between an increase in strength and an actual change in 200-m kayaking performance. In study 1, 37 (22 men and 15 women) elite kayak paddlers performed tests of maximal power output, isometric force, 1 repetition maximum (1RM), and 40 seconds of maximal repetition number in bench press and bench pull and a 30-second all-out on-water sprint kayak test. In study 2, 26 (16 men and 10 women) national elite junior A, U23, and senior kayak paddlers were allocated into 2 groups: a training group (TRAIN) and a maintenance group (MAIN). Each group completed a 6-week strength training intervention with the purpose of either increasing 1RM in bench press (TRAIN) or maintaining strength (MAIN). Pre- and posttests were performed in 200-m kayak ergometer sprint, 1RM bench press, and 1RM bench pull. In study 1, 1RM in bench press was the best predictor of 30-second on-water kayaking performance with a regression coefficient of 0.474. In study 2, TRAIN significantly increased 1RM strength in bench press (pre: 87.3 ± 21.2 kg, post: 93.9 ± 21.3 kg, p = 0.001) and bench pull (pre: 84.2 ± 15.3 kg, post: 86.0 ± 15.1 kg, p = 0.025). In the 200-m kayak ergometer sprint test, TRAIN significantly decreased the time to complete the test (pre: 44.8 ± 4.3 seconds, post: 44.3 ± 4.3 seconds, p = 0.042). In bench press, 1RM was the best predictor of 200-m kayaking, and an increase in bench press 1RM resulted in increased kayaking performance.